BeiDou-GPS integrated dual-system with multi-satellites for positioning and navigating farm vehicles - Caojun, Huang; Jing, Zhao; Chen, Zhao; Boshi, Li; Dekui, Xin (International Journal of Agricultural and Biological Engineering, 2015)
In order to improve the positioning accuracy of self-propelled farm vehicles and to meet the requirements of precision agriculture on the accuracy of machines, a positioning method was proposed based on BeiDou satellite navigation system (BDS) and GPS dual systems with four satellites. The time base and reference coordinates system of BDS and GPS, as well as the transformation between them were discussed in this paper. Two kinds of mathematical models were proposed for the dual-system multi-satellite positioning and dual-system four-satellite positioning. The solution strategies of the proposed model were detailed, and an improved position calculation model of the dual system was developed with modified models. Experimental results demonstrated that the integrated system could enhance the number of visible satellites, expand the scale of the satellite constellation, increase the number of available satellites and improve the positioning accuracy. Besides, the positioning reliability and continuity were also greatly improved.Keywords: precision agriculture, BDS, GPS, integrated positioning, positioning calculationDOI: 10.3965/j.ijabe.20150805.1400Citation: Huang C J, Zhao J, Zhao C, Li B S, Xin D K. BeiDou-GPS integrated dual-system with multi-satellites for positioning and navigating farm vehicles. Int J Agric & Biol Eng, 2015; 8(5): 79－85.